The Influence of Multicultural Education on the Formation of Inclusive and Tolerant Character in Students at MTsN 1 Tana Toraja - Herawaty, Hasmiah; Rahmaniah, Nurul; Zulkarnaen, Moh.; Hariyati (IAIN Parepare, 2025)
This study aims to analyze the influence of multicultural education on the formation of inclusive and tolerant character in students at MTsN 1 Tana Toraja. The background of this research is based on the social conditions of the Tana Toraja community, which is characterized by cultural and religious diversity, thereby requiring educational strategies that foster mutual respect and prevent intolerance. The research method employed is quantitative with a multiple linear regression approach. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, then analyzed using classical assumption tests, F-tests, t-tests, and the coefficient of determination. The results show that multicultural education has a significant effect on the formation of inclusive and tolerant character, both simultaneously and partially. The coefficient of determination (R²) of 0.725 indicates that 72.5% of the variation in the formation of inclusive and tolerant character can be explained by multicultural education, while the remaining 27.5% is influenced by other factors outside the research model. These findings emphasize the importance of integrating multicultural values into the learning process and extracurricular activities to strengthen students’ character, enabling them to adapt to diversity.